(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
The article discusses the fact that folklore is an ancient and historical art of speech, the uniqueness of its genres, the legends of bread, proverbs and their origin. The importance of the artistic means used in myths and proverbs are explained. Here examples are given from folk proverbs about bread